Targeted drug delivery and vaccinology approaches using virus-like particles for cancer - Sereflioglu, Seyma; Yapici, Emine; Sahin, S. Hande Tekarslan; Ozsoy, Yildiz; Ustundag, Cem Bulent (ISTANBUL UNIV, FAC PHARMACY, 2017)
Nanotechnology has the potential to make significant alterations in the treatment of diseases such as cancer through targeted drug delivery nanoparticles. Virus-like particles (VLPs) are composed of the capsid proteins that do not carry the viral genome and are also noninfectious. VLPs are self-assembling competent protein structures with identical or highly related structures to their corresponding native viruses. VLPs that have precise 3D nanostructures exhibit a notable diversity in shapes and structures. They can be produced in large quantities through biological amplification and growth. External protein inserts can be displayed through genetic methods or chemical modifications. Functionalized VLPs when used as delivery systems have the ability to target with specificity and can attract macrophages for the destruction of cancer cells. The capability to target tumors for the delivery of therapeutic agents is an important goal of the design approaches of VLPs. Against the current problems in cancer therapies, delivery systems using VLPs are an arising and promising field with the potential to exhibit solutions. Cancer therapies require specific targeting of the diagnostic element or the drug to tumor cells without binding to or affecting healthy cells and tissues. Specialization of the VLPs provides an opportunity for using them as site-specific drug delivery systems in cancer therapy while reducing the systemic toxicity and the overall damage to healthy cells. With fewer side effects, immunotherapy is also a promising alternative for cancer treatment by primarily activating the host's immune system. Cancer vaccines are aimed at inducing an immune response in the host, thereby generating a defensive mechanism against tumor cells. VLPs can be used as a vaccine without the requirement of any adjuvant due to their naturally optimized particle size and their repetitive structural order. Therefore, the aim of this review is to provide basic information about VLPs and describe previous research on VLPs used as drug and vaccine delivery systems and their applications in different types of cancer.
Keywords: Nanocarriers; virus-like particles; drug delivery; cancer vaccine; cancer therapy; CERVICAL INTRAEPITHELIAL NEOPLASIA; AS04-ADJUVANTED VACCINE; PROTEIN; EFFICACY; NANOPARTICLES; INFECTION; PLATFORM; Pharmacology & Pharmacy